Predictive Value of Neutrophil Lymphocyte Ratio in Assessing Severity Grades of Knee Osteoarthritis : Neutrophil-Lymphocyte Ratio (NLR) an Indicator in Knee Osteoarthritis - Arif, Muhammad Waqar; Niazi, Ghulam Abbas Khan; Amer, Ahsan; Ali, Wasim; Amir, Sehr Zara; Badar, Faizan (Pakistan Journal of Health Sciences, 2024)
<span class="NormalTextRun SCXW165835696 BCX0" data-ccp-parastyle="Normal1" data-ccp-parastyle-defn="{"ObjectId":"22fad7bf-c9a5-44fc-b29d-c09274df223d|216","ClassId":1073872969,"Properties":[469775450,"Normal1",201340122,"2",134233614,"true",469778129,"Normal1",335572020,"1",469777841,"Calibri",469777842,"Calibri",469777843,"Calibri",469777844,"Calibri",469769226,"Calibri",335559740,"259",201341983,"0",335559739,"160",201342446,"1",201342447,"5",201342448,"1",201342449,"1",201341986,"1",268442635,"22",335559704,"1025",335559705,"1033",335551547,"1033"]}">Osteoarthritis is a disease with a significant inflammatory component. Neutrophil Lymphocyte Ratio (NLR) level is a marker to determine inflammation. Objective: To find the value of NLR ratio in assessing severity grades of knee osteoarthritis. Methods: Prospective Observational Study was carried out in Tertiary care hospital on 378 patients diagnosed both clinically and radio graphically with Knee osteoarthritis reported to tertiary care hospital were selected. Convenience sampling was performed. Patients were divided into, group A, B and C Mild, moderate and severe Knee osteoarthritis with 126 patients. Blood samples were taken from participants and total and differential leucocyte counts and neutrophil levels were determined. NLR value was determined in each group. Mean value was calculated. Results: Out of 378 patients, 172 (45.5%) were female and 206 (54.5%) were male. The mean value of NLR ratio in group A was found to be 2.96 ± 0.84. Mean value in group B was found to be 5.83 ± 1.52 and for grade 3 was found to be 8.86 ± 2.33. Conclusions: NLR value is a good indicator for assessing severity grades of Knee osteoarthritis.